Substitution Effect Nutrient Hydroponic with POC Against Plant Growth mustard (Brassica rapa L.) in Hydroponics Wick System in Green House - Ndau, Wensislaus Arman; Sa'adah, Tatuk Tojibatus; Indarwati, Indarwati; Setiawati, Anindya Prastiwi; Bafiqi, Medina Johana Pakula (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2025)
Hydroponics wick system is a hydroponic system by utilizing the wick to absorb water and nutrients by utilizing capillarity power. This axis serves to connect the nutrient solution in the tub with planting medium. This study aims to : (1) determine the effect of the mix AB nutrient on plant growth in hydroponic lettuce; (2) determine the effect of Liquid Organic Fertilizer on plant growth in hydroponic lettuce; (3) the effect of substitution of hydroponic nutrient with a liquid organic fertilizer on plant growth in hydroponic lettuce. This study uses a completely randomized design with 5 treatments and repeated 4 times, resulting in 20 experimental units. The results showed : (1) administration of 5 ml/l A and 5 ml/l B gives the best results in growth of mustard plants; (2) provision of 3 ml/l A and 3 ml/l B + 100 ml/l POC also gave a good response to the growth of mustard plants; (3) administration of 2ml/l A and 2 ml/l B + 150 ml/l POC also gave a good response to the growth of mustard.